iOS wow factor apps and UX design techniques for iPhone and iPad - Wood, Timothy (Apress, 2011)
With the millions of apps in the crowded Apple iTunes App Store, it can be difficult to get your apps noticed. How can you make your app stand out from the crowd and get it the reviews it deserves? iOS Wow Factor shows you how to get noticed! It explains how to go beyond the basics and where to "break the rules" to give your users a "wow" experience! You'll learn to use standard controls, as well as to create non-standard controls and high-impact custom interactions to realize truly compelling app designs. Get grounded in Apple's Human Interface Guidelines (HIG) so that you can appreciate all its wisdom. From that excellent foundation, move beyond the HIG and learn how to ensure that all your apps have that "wow" factor. Learn all about user experience (UX) design techniques, with and beyond Apple's HIG, and how to move your apps out of mundane design and into innovative user experiences. Examine the characteristics and constraints of the iOS platform and how to leverage its strengths to maximum effect in your apps. iOS Wow Factor explains what makes a successful mobile app design, and how to apply those principles of success to your own apps. Once you get the iOS Wow Factor into your apps, you can watch your app adoption rate increase and gain the traction it needs to succeed and earn a profit in the Apple iTunes App Store. Find out everything you'll need to "wow" your future customers!